Dinamika Pertumbuhan Penduduk dalam Mendorong Ekonomi Berkelanjutan - Putri Azkia Risyda; Siti Rahmi; T. Razita Syahinda (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2025)
Population growth is a significant phenomenon in the context of global economic development. This article discusses the dynamics of population growth and its impact on a sustainable economy. Rapid growth can provide opportunities, such as increased labor force and larger consumption markets, but it also brings serious challenges, including pressure on limited natural resources and infrastructure. With an eye on the interaction between population and economy, effective strategies need to be put in place to ensure that population growth becomes an asset, not a burden. Investments in education, sustainable infrastructure development, and inclusive migration policies are key to achieving the desired balance. This article emphasizes the importance of integration between population growth and economic sustainability to build an inclusive and prosperous future for all.